2006
DOI: 10.1590/s0100-84042006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Morfo-anatomia do sistema subterrâneo de Calea verticillata (Klatt) Pruski e Isostigma megapotamicum (Spreng.) Sherff - Asteraceae

Abstract: -(Morpho-anatomy of the subterranean system of Calea verticillata (Klatt) Pruski and Isostigma megapotamicum (Spreng.) Sherff -Asteraceae). Several herbaceous species from "cerrado" (savana like vegetation) have thickened subterranean systems, which may be of root and/or stem nature. These systems have bud shoot-forming potential, providing the sprout of new shoots after an adverse period, like a severe drought or a burning. The verification of the subterranean systems nature is extremely important to the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
2
12
0
3
Order By: Relevance
“…Its structure, ontogenesis and ecological function do not found correspondence with previously subterranean structures described in the international literature, but this term is already accepted by Botanists from other countries who had the opportunity to study Brazilian vegetation, and some Brazilian authors have already employed the term in other studies (Alonso and Machado 2007, Appezzatoda-Glória et al 2008a, Cury and Appezzato-da-Glória 2009. The variation of the xylopodium size and shape verified in the present study was already mentioned by Appezzato-da-Glória et al (2008a) P. alopecuroides and V. elegans, was also reported by Vilhalva and Appezzato-da-Glória (2006) and Appezzato-da-Glória et al (2008a). Plants with the presence of xylopodia showed seasonal growth and, besides the loss of aboveground biomass during the dry season or destruction caused by e.g.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Its structure, ontogenesis and ecological function do not found correspondence with previously subterranean structures described in the international literature, but this term is already accepted by Botanists from other countries who had the opportunity to study Brazilian vegetation, and some Brazilian authors have already employed the term in other studies (Alonso and Machado 2007, Appezzatoda-Glória et al 2008a, Cury and Appezzato-da-Glória 2009. The variation of the xylopodium size and shape verified in the present study was already mentioned by Appezzato-da-Glória et al (2008a) P. alopecuroides and V. elegans, was also reported by Vilhalva and Appezzato-da-Glória (2006) and Appezzato-da-Glória et al (2008a). Plants with the presence of xylopodia showed seasonal growth and, besides the loss of aboveground biomass during the dry season or destruction caused by e.g.…”
Section: Discussionsupporting
confidence: 78%
“…The stemlike origin of xylopodium, as described in M. cordifolia, M. sessilifolia, V. elegans and V. mepapotamica, has already been observed for some other species, such as Isostigma megapotamicum (Spreng.) Sherff (Asteraceae) (Vilhalva and Appezzato-da-Glória 2006); radicular origin, as described in Pterocaulon alopecuroides, was observed for Clitoria guyanensis (Aubl.) Benth (Leguminosae) (Rizzini and Heringer 1961).…”
Section: Discussionmentioning
confidence: 95%
“…Morpho-anatomical studies of the underground systems of plants from the Cerrado have shown the presence of gemmiferous underground systems, such as xylopodia and root buds (Hayashi & Appezzatoda-Gloria 2005, Vilhalva & Appezzato-da-Gloria 2006. Alonso & Machado (2007) described the morpho-anatomy and sprouting ability of the underground system of Erythroxylum species in the Cerrado.…”
Section: Resultsmentioning
confidence: 99%
“…Brazilian species from this genus occur mainly in the Cerrado regions in climates that have dry winters (Magenta et al, 2010), and these species are most often observed under such conditions that may be related to the type of thickened underground system, which supports the plants' water needs during dormancy (Zaidan and Carreira, 2008;Magenta et al, 2010) and is essential for regenerating the vegetative aerial portions (Oliveira et al, 2013;Bombo et al, 2014). The thickened underground systems, which can bear buds, were observed in other Asteraceae species, and these systems may be morphologically diverse, such as xylopodia, rhizophores, root buds and diffuse underground systems (Vilhalva and Appezzato-da-Glória, 2006;Hayashi and Appezzato-da-Glória, 2007;Appezzato-da-Glória et al, 2008;Appezzato-da-Glória and Cury, 2011). However, it has been observed that some species cannot propagate vegetatively even bearing a thickened underground system, and the sexual reproduction ensures maintenance of the species (Cury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%